2019
DOI: 10.1039/c9fo00558g
|View full text |Cite
|
Sign up to set email alerts
|

Multicompartment emulsion droplets for programmed release of hydrophobic cargoes

Abstract: Multi-compartmentalized microdroplets composed of a multiple subcompartment shell and single microscale host compartment core were prepared facilely for achieving programmed release of hydrophobic cargoes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Furthermore, wrinkling of the aqueous solution containing QS occurred and wrapped outside the oil drop to form the “crosslinked network” (see arrow), which further confirms the self-assembly of QS at the oil–water interface of the adjacent saponin molecules. This led to the locking together by self-assembled crosslinking between the molecules and provided a firm basis for the formation of simultaneously stabilizing emulsions and providing hierarchy comparts. ,, …”
Section: Experimental Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, wrinkling of the aqueous solution containing QS occurred and wrapped outside the oil drop to form the “crosslinked network” (see arrow), which further confirms the self-assembly of QS at the oil–water interface of the adjacent saponin molecules. This led to the locking together by self-assembled crosslinking between the molecules and provided a firm basis for the formation of simultaneously stabilizing emulsions and providing hierarchy comparts. ,, …”
Section: Experimental Results and Discussionmentioning
confidence: 99%
“…This led to the locking together by selfassembled crosslinking between the molecules and provided a firm basis for the formation of simultaneously stabilizing emulsions and providing hierarchy comparts. 18,19,26 A minimization of interfacial free energy between the interface of two immiscible liquids is believed to be the driving force for selfassembly. 27 Presumably the self-assembly of QS absorbing and organizing at the oil−water interface forms a solid-like layer in a closely packed array and "surface skin".…”
Section: ■ Experimental Results and Discussionmentioning
confidence: 99%
“…Emulsions were first produced by emulsification in a one-pot strategy, according to the process described in our previous work ( Chen, et al, 2019 ). Briefly, soybean oil (at a fixed of 75 wt%), Quillaja saponin (1.5 wt%), glycyrrhizic acid (0.5–2.0 wt%) and phosphate-buffered saline (PBS, 20 mM, pH 7.0) were mixed.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the QS extracts can provide positive effects on the inhibition of lipid oxidation in in oil-in-water emulsions [ 85 ], and the emulsions also can be used to control flavor retention and release during simulated cooking [ 86 ]. Chen et al recently reported that the nanodroplets stabilized by QS can further serve as building blocks for fabricating microscale emulsion droplets, which display multicompartment architectures comprised of many nanodroplets as an interfacial shell and a single microdroplet core ( Figure 3 ) [ 87 ]. They found that the prepared multicompartment emulsion droplets can allow the programmed release of various volatile compounds by controlling the number of the QS-based nanodroplets around the surfaces of microdroplets, which can accurately manipulate the interfacial permeability ( Figure 3 ).…”
Section: Applications Of Saponins In Colloidal Multiphase Systemsmentioning
confidence: 99%
“… Schematic illustration of the mechanism for programmed release of hydrophobic cargoes from the multicompartment microdroplets stabilized by Quillaja saponin (QS)-coated nanodroplets. Images were reproduced with permission from [ 87 ]. …”
Section: Figurementioning
confidence: 99%